The applicability of the 1980 Hague Abduction convention in Muslim countries: a particular reference to the Malaysian position - Hamid, Abdul Ghafur@Khin Maung Sein; Abdul Hak, Nora; Mohd Zin, Najibah (2017)
In response to the increasing number of traumatic international child abduction cases, the Hague Abduction Convention has been adopted to secure the return of the abducted child to the country of his habitual residence. Most of the Muslim countries are, however, not yet parties to the Convention. This paper seeks to investigate the reason for this phenomenon, focusing in particular on the compatibility of the Convention with basic tenets of Islamic law. The paper further evaluates the Malaysian domestic legislation and case law in order to ensure whether it is in a position to be a party to the Convention. The paper finds that although there are a few areas of concern, no serious incompatibility between Shari’ah and the Convention exist and that more dissemination is required to quash misconceptions about the Convention among Muslim countries. The paper concludes with recommendations for Muslim countries in this crucial area of protecting the best interests of our children.